Dinamika dan Profil Undecided Voters Menjelang Pemilu 2024 di Indonesia - Priyatno, Vincentius Gitiyarko (Universitas Tribhuwana Tungga Dewi, 2024)
Leading up to the 2024 elections, the public is starting to show their political preferences for both presidential candidates and political parties. However, there is still a portion of the population that hasn't disclosed their choices. Unlike abstaining from voting (golput), this position is more temporary, given that there is still time to consider their options for the upcoming elections. In surveys, this position is indicated by responses such as